Needs Assessment of Beneficiaries in the “Adopt-A-Trainee” Program of the University - Bachanicha, Rafael; Dorio Jr., Policronio; Taoc, Margarette (JPAIR Multidisciplinary Research, 2025)
This study determines and explores the training needs of the beneficiaries of the adopted community of the university as an integral part of its community extension services. The study focused on assessing the beneficiaries’ employable skills and employed a descriptive quantitative survey research method to determine the needs. There were 82 respondents in this study who were currently residing in the communities adopted by the university. Sampling techniques like convenience and snowballing were utilized to gather the desired data. The primary goal of this study was to assess the beneficiaries’ current needs, which will be used to establish programs and activities for the University of Cebu LM Campus College Of Hospitality and Tourism Management’s community extension services. The skills training for the entire duration includes food and beverage services, food production, food safety, housekeeping services, front office services, catering services, events management, and public area cleaning. Furthermore, this study sheds light on why the beneficiaries participate in the "Adopt-A-Trainee" program of the university. Through this study, the university was able to design a comprehensive training program specifically for the beneficiaries, making them skilled and employable individuals. Finally, this study served as the basis for future community extension programs to the adopted communities of the university.